1986
DOI: 10.3109/00498258609043556
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanol ingestion on the metabolism of a hepatotoxic dose of paracetamol in mice

Abstract: After administration to mice of a hepatotoxic dose of paracetamol (400 mg/kg body wt, p.o.) peak plasma concentrations of the drug and its glucuronide were approximately 900 microM around one hour. Corresponding levels of the sulphate, mercapturate and cysteine conjugates were approximately 100, 35 and 20 microM, respectively. Urinary excretion accounted for 55% of the administered drug 31 h after dosing. Of this total, 64.7% was paracetamol glucuronide, 17.9% paracetamol cysteine, 10.4% paracetamol sulphate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…While chronic ethanol increases risk from acute paracetamol dosing (121,189,214) on the basis of induced P450 paracetamol metabolism, and consequent increased formation of NAPQI, or decreased glutathione supply or hepatic regeneration power (118), acute ethanol coadministration with paracetamol may be somewhat hepatoprotective (212,214) presumably by competitive inhibition of P450 paracetamol metabolism to NAPQI.…”
Section: Toxicologymentioning
confidence: 99%
“…While chronic ethanol increases risk from acute paracetamol dosing (121,189,214) on the basis of induced P450 paracetamol metabolism, and consequent increased formation of NAPQI, or decreased glutathione supply or hepatic regeneration power (118), acute ethanol coadministration with paracetamol may be somewhat hepatoprotective (212,214) presumably by competitive inhibition of P450 paracetamol metabolism to NAPQI.…”
Section: Toxicologymentioning
confidence: 99%
“…When a single dose of ethanol is given at or about the same time as paracetamol, it protects animals against hepatotoxicity even if they have been sensitized by previous chronic administration of alcohol [71, 78, 81, 85, 129–134] . This protective effect is associated with inhibition of the toxic metabolic activation of paracetamol both in vivo [79, 82, 134–136] and in vitro [136, 137]. Ethanol protects at concentrations as low as 2 m m [137] but once it has disappeared from the system, paracetamol metabolism reverts to the previous state.…”
Section: Acute Vs Chronic Ethanolmentioning
confidence: 99%
“…However, there have been some anomalous findings. Thus chronic ethanol did not always cause induction [76, 81, 82, 143], and hamsters treated with chronic ethanol and then withdrawn from it for 24 h were more resistant to the toxicity of paracetamol than control animals not exposed to ethanol [76]. Nevertheless, the potentiation of the hepatotoxicity of paracetamol by chronic ethanol intake in animals forms the mainstay of the belief that there is similar enhancement of toxicity in chronic alcoholics.…”
Section: Acute Vs Chronic Ethanolmentioning
confidence: 99%
“…When ethanol is administered in a single dose or when it is administered long term to experimental animals and continued as acetaminophen is administered, decreased acetaminophen toxicity and a decrease in the formation of NAPQI are observed. [25][26][27][28][29] In experimental studies in nonalcoholic human subjects, inhibition of NAPQI formation is observed when ethanol is ingested with acetaminophen, consistent with the studies in animals.30 Studies in rats, mice, and baboons show that if enough time is allowed between the last dose of ethanol and the administration of acetaminophen for ethanol to be eliminated, long-term administration of ethanol enhances the formation of NAPQI in vivo, and that microsomes prepared from animals receiving multiple-dose ethanol also show enhanced NAPQI formation. 26,31"4 Similarly, if ethanol is interrupted for at least 12 hours in alcoholic patients, acetaminophen toxicity, CYP2El activity, and formation of NAPQI are increased.…”
Section: Effects Of Single-and Multiple-dose Ethanol On Acetaminophenmentioning
confidence: 99%